Kinetika Reaksi Upgrading Bio-oil Melalui Proses Esterifikasi dengan Katalis Biochar Tersulfonasi - Febriantoni Febriantoni; Sunarno; Panca Setia Utama (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2026)
Development and research related to the utilization of biomass is currently motivated by the depletion of fossil fuel resources. Bio-oil from palm fronds, which is expected to be a renewable energy, can be produced through pyrolysis. However, bio-oil cannot be used directly as fuel because it contains many mixed compounds. Therefore, upgrading with esterification process using variable temperature and sulfonated biochar catalyst is a solution offered in improving the quality of bio-oil. This research studied the kinetics of esterification reaction using sulfonated biochar catalyst and temperature variations (40 °C, 50 °C, 60 °C and 70 °C), 4% catalyst concentration, 5:1 molar ratio of methanol: bio-oil to obtain the effect of catalyst use on the temperature used and obtain the reaction rate equation from the use of catalyst based on the validated reaction order. The results concluded that the sulfonated biochar catalyst characterized by SEM test and FTIR test, showed the success of -SOɜH bond and showed the expected changes in surface morphology. The esterification reaction kinetics for bio-oil upgrading with sulfonated biochar catalyst is a pseudo second-order reaction with a value of R² = 0.9483 (valid at a reaction time of 0-60 minutes, if more than that time does not describe the initial kinetic phase) with the reaction rate equation